Proceedings of the International Conference on Biology, Sciences and Education (ICoBioSE 2019) 2020
DOI: 10.2991/absr.k.200807.054
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Rhodamine B from Aqueous Solution Using Langsat (Lansium domesticum) Shell Powder

Abstract: The potensial of langsat (Lansium domesticum) shell powder to adsorb rhodamine B from aqueous solution has been investigated through bath experiments. The rhodamine B adsorption was found to be dependent on pH, initial rhodamine B concentration. The equilibrium data were described by Freundlich and Langmuir with the maximum adsorption capacity was 2,1531 mg/g in a pH 5. While the optimum concentration at 100 ppm with a capacity of 12,3743 mg/g. In order to know the biosorption mechanism FT-IR analyses were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…Biosorben serbuk kulit durian (Durio zibethinus L.) dianalisis dengan FTIR untuk menentukan gugus fungsi yang terikat pada ion Cu 2+ . Hasil FTIR sampel sebelum diaktivasi, sesudah di aktivasi dan sesudah dikontakkan dapat dilihat pada Gambar 1. yang teradsorpsi akan semakin banyak sampai pada suatu titik, dimana seluruh situs aktif pada biomassa telah jenuh oleh Cu 2+ , sehingga jumlah Cu 2+ yang terikat mengalami penurunan, seperti yang terjadi pada waktu 120 menit dengan kapasitas penyerapan 12,171 mg/g yang mana permukaan biosorben dalam kondisi jenuh sehingga sedikit demi sedikit situs aktif yang berinteraksi dengan ion logam mulai melepaskan ion logam kembali kedalam larutan (Adella & Kurniawati, 2020).…”
Section: Karakterisasi Ftirunclassified
“…Biosorben serbuk kulit durian (Durio zibethinus L.) dianalisis dengan FTIR untuk menentukan gugus fungsi yang terikat pada ion Cu 2+ . Hasil FTIR sampel sebelum diaktivasi, sesudah di aktivasi dan sesudah dikontakkan dapat dilihat pada Gambar 1. yang teradsorpsi akan semakin banyak sampai pada suatu titik, dimana seluruh situs aktif pada biomassa telah jenuh oleh Cu 2+ , sehingga jumlah Cu 2+ yang terikat mengalami penurunan, seperti yang terjadi pada waktu 120 menit dengan kapasitas penyerapan 12,171 mg/g yang mana permukaan biosorben dalam kondisi jenuh sehingga sedikit demi sedikit situs aktif yang berinteraksi dengan ion logam mulai melepaskan ion logam kembali kedalam larutan (Adella & Kurniawati, 2020).…”
Section: Karakterisasi Ftirunclassified
“…The results showed that the absorption of Pb metal ions for longan peel and longan seeds reached 42.14% and 57.07%, and Cd metal ions for seeds and longan shells reach 68.11% and 64.77%. The potential of langsat shell powder (Lansium domesticum) to adsorb rhodamine-B with an adsorption capacity of 12.3743 mg/g (Adella and Kurniawati , 2020).…”
Section: Introductionmentioning
confidence: 99%